Integrative Insights into the Myoelastic-Aerodynamic Theory and Acoustics of Phonation. Scientific Tribute to Donald G. Miller - Švec, Jan G; Schutte, Harm K; Chen, C Julian; Titze, Ingo R (Journal of voice, 2023)
In this tribute article to D.G. Miller, we review some historical and recent contributions to understanding the myoelastic-aerodynamic (MEAD) theory of phonation and the related acoustic phenomena in subglottal and vocal tract. At the time of the formulation of MEAD by van den Berg in late 1950s, it was assumed that vocal fold oscillations are self-sustained thanks to increased subglottal pressure pushing the glottis to open and decreased subglottal pressure allowing the glottis to close. In vivo measurements of subglottal pressures during phonation invalidated these assumptions, however, and showed that at low fundamental frequencies subglottal pressure rather tends to reach a maximum value at the beginning of glottal closure and then exhibits damped oscillations. These events can be interpreted as transient acoustic resonance phenomena in the subglottal tract that are triggered by glottal closure. They are analogous to the transient acoustic phenomena seen in the vocal tract. Rather than subglottal pressure oscillations, a more efficient mechanism of transfer of aerodynamic energy to the vocal fold vibrations has been identified in the vertical phase differences (mucosal waves) making the glottal shape more convergent during glottis opening than during glottis closing. Along with other discoveries, these findings form the basis of our current understanding of MEAD.
Keywords: Subglottal resonances Vocal tract resonances; Vocal Cords; akustika; biomechanika; Humans; Glottis; fonace; Acoustics; glottis; lidé; Biomechanical Phenomena; Voice production Vocal fold vibration; Vibration; Phonation; Myoelastic-aerodynamic theory of phonation; vibrace; hlasové řasy